Utilization of Pipeline embolization device for treatment of ruptured intracranial aneurysms: US multicenter experience. (17th September 2014) - Lin, Ning; Brouillard, Adam M; Keigher, Kiffon M; Lopes, Demetrius K; Binning, Mandy J; Liebman, Kenneth M; Veznedaroglu, Erol; Magarik, Jordan A; Mocco, J; Duckworth, Edward A; Arthur, Adam S; Ringer, Andrew J; et al.
Abstract : Objective: Utilization of the Pipeline embolization device (PED) in complex ruptured aneurysms has not been well studied. We evaluated the safety and effectiveness data from five participating US centers. Methods: Records of patients with ruptured cerebral aneurysms who underwent PED treatment between 2011 and 2013 were retrospectively reviewed. Results: 26 patients with ruptured aneurysms underwent PED treatment (mean age 51.4±13.2 years;16 women). At presentation, 8 patients (30.8%) had a Hunt–Hess grade of IV or above; 11 required extraventricular drain placement. Aneurysm morphologies were: 8 dissecting, 8 blister-like, 6 fusiform, and 4 saccular. There were 22 anterior circulation and 4 posterior circulation aneurysms. PED deployment was successful in all patients, with adjunctive coiling utilized in 12. Periprocedural complications occurred in 5 (19.2%), including 3 inhospital deaths. 23 patients (88.5%) had postoperative angiography at a mean of 5.9 months: 18 aneurysms (78.3%) were completely occluded, 3 (13.0%) had residual neck filling, and 2 (8.7%) had residual dome filling. All blister-type aneurysms were completely occluded at follow-up. Clinical follow-up was available for an average of 10.1 months (range 2–21 months), with one asymptomatic in-stent stenosis and one asymptomatic thromboembolic stroke noted. Good outcome (modified Rankin Scale (mRS) score of 0–2) was achieved in 20 patients (76.9%), fair (mRS 3–4) in 3 (11.5%), and 3 died (11.5%). Conclusions: The PED can be utilized for ruptured aneurysms and is a good option for blister-type aneurysms. However, due to periprocedural complications, it should be reserved for lesions that are difficult to treat by conventional clipping or coiling.